2018
DOI: 10.1111/cdev.13083
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Socializing Preferences in Hong Kong Chinese Children

Abstract: The impact of social group information on the learning and socializing preferences of Hong Kong Chinese children were examined. Specifically, the degree to which variability in racial out-group exposure affects children's use of race to make decisions about unfamiliar individuals (Chinese, White, Southeast Asian) was investigated. Participants (N = 212; M = 60.51 months) chose functions for novel objects after informants demonstrated their use; indicated with which peer group member to socialize; and were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…It is also possible that implicit and explicit racial biases might be affected by different factors. Implicit racial bias may be influenced to a greater extent by direct perceptual experiences, such as different levels of exposure to own- and other-race faces (Prestwich, Kenworthy, Wilson, & Kwan-Tat, 2008), racial diversity in children’s daily environment (Chen et al, 2018; McGlothlin & Killen, 2006), and the expertise to recognize and differentiate between own- and other-race people (Qian et al, 2017a, 2017b; Xiao et al, 2015). Explicit racial bias, on the other hand, may be more vulnerable to social interactions, such as interracial friendship and social learning from parents and peers (Gawronski & Bodenhausen, 2006; Pettigrew & Tropp, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that implicit and explicit racial biases might be affected by different factors. Implicit racial bias may be influenced to a greater extent by direct perceptual experiences, such as different levels of exposure to own- and other-race faces (Prestwich, Kenworthy, Wilson, & Kwan-Tat, 2008), racial diversity in children’s daily environment (Chen et al, 2018; McGlothlin & Killen, 2006), and the expertise to recognize and differentiate between own- and other-race people (Qian et al, 2017a, 2017b; Xiao et al, 2015). Explicit racial bias, on the other hand, may be more vulnerable to social interactions, such as interracial friendship and social learning from parents and peers (Gawronski & Bodenhausen, 2006; Pettigrew & Tropp, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests that by preschool age, children already associate race and wealth (an indicator for social status) and prefer racial groups who are rich (Mandalaywala, Rhodes, & Tai, 2019;Newheiser et al, 2014;Olson, Shutts, Kinzler, & Weisman, 2012;Rudman, Feinberg, & Fairchild, 2002). Chen, Corriveau, Lai, Poon, and Gaither (2018) found that 4-to 6-year-olds from Hong Kong preferred higher status outgroup Whites to lower status outgroup Southeast Asians. There is also some evidence suggesting that children's preference for high status individuals relates to their racial preferences: Newheiser and Olson (2012) found that 7to 11-year-old Black American children's preference for wealthy people was associated with an implicit preference for Whites (see also Newheiser et al, 2014).…”
mentioning
confidence: 98%
“…Comparing Chinese children’s gender brilliance stereotype about Asians to that of White people presents a compelling context to tease apart the two social factors. Asians are the racial majority in China, and yet they are associated with lower social status relative to White people with relation to historical reasons (Chen et al, 2018; Goon & Craven, 2003; Lan, 2016; Qian et al, 2016, 2019; Stohry et al, 2021). For example, Chinese adults perceived White people as obtaining higher education and more prestigious jobs than Asians (Qian et al, 2016), and Chinese children became more likely to match expensive possessions with Whites than Asians with age (Qian et al, 2019).…”
Section: The Early Emergence Of the Gender Brilliance Stereotypementioning
confidence: 99%
“…Although the drive to affiliate with socially similar others is considered to be a fairly ubiquitous phenomenon (Meltzoff 2007), some researchers have emphasized the role of early sociocultural experiences in the development of in-group positivity. For example, minority race children can exhibit less favoritism for in-group members compared with majority (white) children (Margie et al 2005;Shutts et al 2011), and variability in socialization with and exposure to different racial groups can shape young children's social preferences (Chen et al 2018;Gaither et al 2014).…”
Section: Moral Rigidity As An Error Management "Bias"mentioning
confidence: 99%